1998
DOI: 10.1111/j.1445-5994.1998.tb04452.x
|View full text |Cite
|
Sign up to set email alerts
|

Short duration therapy for Helicobacter pylori in Western Australia: the impact of metronidazole resistance

Abstract: In Western Australia clearance rates of H. pylori infection, after one week of BTM or LAM, are lower than in other published series. The high incidence of metronidazole resistance is the main determinant of our relatively poor eradication rates.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

2
6
1
3

Year Published

1999
1999
2015
2015

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 24 publications
(12 citation statements)
references
References 0 publications
2
6
1
3
Order By: Relevance
“…Patients harbouring H. pylori strains resistant to metronidazole had H. pylori cure rates significantly lower than patients with H. pylori metronidazole‐sensitive strains when treated with regimens which included metronidazole (PAM and PCM). These data are in agreement with other studies which demonstrated significantly lower H. pylori cure rates in metronidazole‐resistant patients after treatment with metronidazole in triple therapies which included a proton pump inhibitor and amoxycillin, 12 –17 a proton pump inhibitor and clarithromycin, 14 , 18 , 19 colloidal bismuth subcitrate and amoxycillin, 20 –22 as well as in quadruple therapy with omeprazole, colloidal bismuth subcitrate and tetracycline 23 . In conflict with the present results and with those of the above‐cited reports, 14 , 18 , 19 some studies failed to find a negative influence of metronidazole resistance on the clinical efficacy of a proton pump inhibitor‐based triple therapy which included metronidazole (or tinidazole) in combination with clarithromycin 12 , .…”
Section: Discussionsupporting
confidence: 92%
“…Patients harbouring H. pylori strains resistant to metronidazole had H. pylori cure rates significantly lower than patients with H. pylori metronidazole‐sensitive strains when treated with regimens which included metronidazole (PAM and PCM). These data are in agreement with other studies which demonstrated significantly lower H. pylori cure rates in metronidazole‐resistant patients after treatment with metronidazole in triple therapies which included a proton pump inhibitor and amoxycillin, 12 –17 a proton pump inhibitor and clarithromycin, 14 , 18 , 19 colloidal bismuth subcitrate and amoxycillin, 20 –22 as well as in quadruple therapy with omeprazole, colloidal bismuth subcitrate and tetracycline 23 . In conflict with the present results and with those of the above‐cited reports, 14 , 18 , 19 some studies failed to find a negative influence of metronidazole resistance on the clinical efficacy of a proton pump inhibitor‐based triple therapy which included metronidazole (or tinidazole) in combination with clarithromycin 12 , .…”
Section: Discussionsupporting
confidence: 92%
“…Over recent years, shorter triple therapy protocols have been used with the intention of reducing side‐effects and perhaps increasing compliance with treatment. However, with the increasing incidence of antibiotic resistance [5], it appears that the most practical way of controlling and eliminating H. pylori will be through the development of effective protein‐based vaccines. There is now sufficient experimental data to indicate that this goal is achievable [6].…”
mentioning
confidence: 99%
“…O insucesso dos tratamentos endodônticos também tem sido associado à resistência dos micro-organismos patogênicos aos medicamentos utilizados para combatê-los. Esse mecanismo de resistência resulta de alterações fisiológicas ou estruturais da célula bacteriana, que representa uma estratégia de sobrevivência ao ataque abusivo dos agentes antimicrobianos 12 . Estudos têm revelado um aumento surpreendente da resistência antimicrobiana das bactérias que são comumente encontradas nos canais radiculares de dentes com infecção endodôntica.…”
Section: Introductionunclassified